PROFESSIONAL AND PSYCHOLOGICAL SELECTION OF SPECIALISTS AS THE BASIS OF PROFESSIONAL SUITABILITY AND PROFESSIONAL WELL-BEING OF AN INDIVIDUAL (Psychology Travelogs, 2025)
The article defines that professional and psychological selection contributes to the formation of an adequate professional suitability of an individual, which determines job satisfaction and the professional well-being of a specialist. At the same time, scientific principles of systemacity, complexity, dynamism, activity and differentiation, used in the research, are presented.It has been identified that the issue of professional suitability within the system of professional and psychological selection is essentially a problem of mutual adaptation of a person to an activity. In other words, ensuring the suitability of the activity itself for the person is considered an anthropocentric approach. At the same time, the assessment and formation of a person’s suitability for a specific activity or group of activities is interpreted as a profesiocentric approach. It has been established that the process of forming professional suitability within the structure of professional and psychological selection goes through several stages. These stages include the following areas: professional education and training, career guidance, professional selection, as well as professional preparation, adaptation, work activity, certification, rehabilitation, and well-being.It has been determined that professional well-being is achieved as a result of the fullest realization of a person in a specific activity, as well as the fulfillment of life and professional goals. An individual's professional suitability fosters the growth of abilities, personal characteristics, and professionally important qualities. This, in turn, encourages the acquisition of new types of activities and creative engagement in performing professional duties.
Keywords: professional and psychological selection; formation; suitability; well-being; working conditions; scientific potential